PERAN KUALITAS AUDIT DALAM MEMITIGASI DAMPAK TAX RISK TERHADAP NILAI PERUSAHAAN - Dede Monikasari; Nurul Aisyah Rachmawati (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
This study aims to examine the impact of tax risk on firm value, with audit quality serving as a moderating variable. The population for this research includes manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sampling method employed is purposive sampling. The data used are secondary, collected from www.idx.co.id and https://finance.yahoo.com. The findings indicate that tax risk has no significant effect on firm value. Additionally, audit quality does not significantly moderate the relationship between tax risk and firm value. These results suggest that investors have not fully regarded tax risk or audit quality as key factors in evaluating firm value within the manufacturing sector.